The Effect of Unemployment Insurance on Unemployment Duration - Ben-Horim, Moshe; Zuckerman, Dror (Journal of Labor Economics, 1987)
This paper shows that unemployment insurance benefits could decrease the expected duration of unemployment induced by search. An unemployed person who has to finance search from limited resources may use the benefits to intensify search effort and lower the expected duration of unemployment.